DEVELOPING A CHARACTER BASED MODULE FOR LEARNING PANCASILA AND CIVICS EDUCATION AT GRADE VII SMP - Sudiyo Widodo; Sri Wiyata (JURNAL PAJAR (Pendidikan dan Pengajaran), 2020)
Modules refer to teaching materials arranged systematically and attractively which include contents, methods, and learning evaluation. A module can be used independently by students to achieve the expected competencies. The purpose of this study was to determine the extent to which the Pancasila and Civics Education module with character-based learning approach for grade VII junior high school students could be used especially in developing or forming the students’ characters. This module was expected to assist grade VII students to have better characters. This research was Research and Development since it  developed a character-based approach module. R&D aims to develop a new product or to improve an existing product. The results of this study found that the character-based learning at grade VII was less optimal and did not contain noble values. As a result, the students’ character was not well-built so research on character-based module for grade VII SMP needed to be developed. The subjects of this research were 35 grade VII students in the first semester of the academic year 2018/2019. The results revealed that 25 students were active in the learning process and most of them had reached the KKM score of 85%. Meanwhile, the students’ comprehension about the language was 82.5%. Thus, the character-based module assisted students to achieve good grade in learning Pancasila and Civics Education.